Unternehmensdaten: Nutzbarkeit verbessern - Sandra Gottschalk; Carla Krolage; Georg Licht; Andreas Peichl; Sandra Schaffner; Sebastian Wichert (Wirtschaftsdienst, 2023)
– High-quality company data is crucial for state-of-the-art empirical research and competition, as well as for evidence-based policy advice, reliable forecasts and policy evaluations. In Germany, however, there are striking deficits in the availability of and access to company data compared to other European countries. This leads to disadvantages in scientific competition, but above all to major welfare losses for the German economy and society as a whole. The planned Research Data Act is intended to remedy the situation. This article proposes four key measures in the area of company data to sustainably improve research and policy evaluation in Germany.
Keywords: C80; D22; 330